Implementation of flipped learning with flipbook media assistance on learning outcomes and critical thinking abilities - Diah Sudiarti; Nashlul Muflihatul Ashilah; Umi Nurjanah (Jurnal Inovasi Teknologi Pendidikan, 2023)
This research was conducted as a sort of classroom action research with two learning cycles to examine whether flipped learning aided by flipbook media may enhance students' cognitive learning outcomes and critical thinking skills. This research's population consisted of tenth-grade Madrasah Aliyah Al Misri Curahmalang students for the academic year 2021-2022. Methods for collecting data include interviews, tests, observations, and documentation. The classical completeness of cognitive learning outcomes increased from 19% in the first cycle to 97% in the second cycle, according to the research findings. Whereas critical thinking abilities were acquired in the first cycle, just one student met critical criteria. In contrast, six students exceeded crucial criteria, and twenty students exceeded critical criteria in the second cycle.  Based on the analyzed research findings, it is possible to conclude that flipped learning aided by flipbook media can enhance students' cognitive learning outcomes and critical thinking skills.